STUDI STRUKTUR PASAR INDUSTRI KARAOKE DI KOTA KENDARI - Rosnawintang Rosnawintang (JEP (Jurnal Ekonomi Pembangunan), 2016)
This study aims to analyze and determine the market structure of the karaoke industry in the Kendari City. The type of data used in this study is primary taken directly to the field, namely directly to the karaoke entertainment business by means of observation. Data analysis with market share, concentration ratio, and entry barries. Based on the results of the study showed that the market structure of the karaoke industry in Kendari City is classified as a tight oligopoly market structure. This market structure indicates that there is a high level of concentration, medium to high sized entry conditions and homogeneous product types.